Low cost method and apparatus for fracturing a subterranean formation with a sand suspension - Justus, Donald M; Ritter, David Wesley; Vitthal, Sanjay (2006)
The present invention is directed to a low cost method and apparatus for fracturing a subterranean formation. The invention involves using a centrifugal pump to combine a fracture fluid, a sand suspension and liquid additive and discharge a mixture of these components into a high pressure pump that injects the mixture into the subterranean formation. The apparatus employs a control pinch valve to precisely control the amount of sand suspension being added to the mixture. The apparatus eliminates the need for expensive blenders, other equipment and associated personnel and provides a low cost means of fracturing the subterranean formation.